(untitled) (Palíndromo, 2025)
Architecture in the Construction of Aesthetic Experiences in the Galleries of the Instituto Inhotim is a research focused on the investigation of contemporary exhibition spaces and the sensory relationships established between users and the artworks on display. Based on practical and theoretical analyses, the work is structured on phenomenological foundations to discuss the architectural, aesthetic, and sensory quality of the spaces addressed, as well as to support the development of a repertoire of design strategies. The study explores five galleries at Inhotim: True Rouge, Doug Aitken, Matthew Barney, Valeska Soares, and Lygia Pape. The method employed involves the integration of a theoretical framework, composed of writings by Juhani Pallasmaa, Maurice Merleau-Ponty, and Jonathan Crary, with field visits documented through photographs and interviews with Inhotim’s technical collaborators. This initial survey was organized into process diagrams and contributed to the critical development of the present work. The analyses identified symbolic and structural strategies, such as the use of form, materiality, and lighting to construct narratives that introduce the artworks, as well as to manipulate attention through sensory perception across the various spatial scales. The research contributes to the advancement of the fields of exhibition design, contemporary art, and monumental architecture.